Autokommunikation. Hvad er det? - Mikkelsen, Jan Foght (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2019)
Auto-communication is communication directed to the sender himself or herself, but communicated via the outside world in an external media with a self-corroborating function. Auto-communication is an overlooked phenomenon in media and communication research. Therefore, the purpose of this article is to examine the phenomenon of auto-communication as a special type of communication by stating its specific textual traits and its function for the sender: to stimulate the self-esteem and to confirm the identity. The article distinguishes between an unreflected auto-communication and a planned and strategic use of auto-communication. Autocommunication exists on an organizatorial level, for example, in self-referential and inside advertisings which are irrelevant to the consumer. Auto-communication also exists on an individual level, for example in personal updatings on Facebook, which are only relevant to the sender because of the egocentric, superficial and trivial character of the content.